Beta2-agonists and physical performance: A systematic review and meta-analysis of randomized controlled trials - Pluim, B. M.; de Hon, O.; Staal, J. B.; Limpens, J.; Kuipers, H.; Overbeek, S. E.; Zwinderman, A. H.; Scholten, R. J. P. M (Sports Medicine, 2011)
Inhaled Beta2-agonists are commonly used as bronchodilators in the treatment of asthma. Their use in athletes, however, is restricted by anti-doping regulations. Controversies remain as to whether healthy elite athletes who use bronchodilators may gain a competitive advantage.